Gamificação como instância da reontologização tecnológica - Danilo Frambach (O Que Nos Faz Pensar)
The present work aims to examine the relationship between gamefication and the process of reontologization of the world promoted by technological advancement, as proposed by Floridi. This process would reconfigure the nature of the world in such a way that artificial systems can be considered to have agency. Our hypothesis follows: (a) the reontologization process can only occur when we assume a solutionist view of the world; (b) gamefication has clear elements of solutionism, and as a technological element, it is part of this reontologization; and thus, (c) gamefication ends up being appropriated by capitalism as a way to conceal exploitative processes behind game elements. Therefore, the article aims to conclude with an analysis of the metaphor of mistification, as a way in which Big Techs utilize gamefication.